American English and British English: Vocabulary and Grammar Differences - Barata, Paga Tri (Journal of Language Intelligence and Culture, 2020)
American English and British English are the famous English varieties in the world, although there are lots of varieties in English, but AmE and BrE are the most famous, they have lots of differences each other and sometimes those differences make the new learner confused. This research examines about Grammar and Vocabulary differences between American and British English. The researcher uses Qualitative Approach in this research because the researcher explains the results of research in words form, while Library Research is type of research that researcher used, because the sources of this research are several books, articles and others. The findings of this research indicated that are many differences between American English and British English including in the aspects and grammar and vocabulary. The differences are not a big deal for native speakers, but they may confuse non-native speakers of English.